The The Strategic Role of Kiai in Embedding Qur'anic Educational Values within Rural Communities - Zainal Arifin; Sholihul Huda; Mohammad Hasan Bisyri; Mamdukh Budiman (Edukasia Islamika : Jurnal Pendidikan Islam, 2025)
Grounding Qur'anic values means actualizing Qur'anic teachings in the context of real life in society. Kiai have a strategic role as guardians of morality and bastions of Qur'anic values. They are able to reorient the values of society in a subtle but effective way, such as through ta’lim assemblies, Friday sermons, and through daily social interactions. However, it cannot be denied that the strategic role of kiai in grounding Qur'anic values faces various challenges. This research uses a qualitative approach with a case study method. This approach was chosen because it is able to explore in depth the complex and contextual social realities related to the strategic role of kiai in grounding Qur'anic values in the lives of rural communities. Various research findings include Kia Huda's community base and social network, strategies for grounding Qur'anic values and thematic analysis of findings in the field. Social role, Kiai Huda is considered a central figure in solving social and spiritual problems of the community. Kiai Huda's da'wah strategy uses local language and a family approach. Residents feel very close to Kiai Huda by responding enthusiastically to his da'wah. The community becomes more open, harmonious and responsive to Islamic values in daily life as a result of the Qur'anic values provided by Kiai Huda. The strategic role of kiai in grounding Qur'anic values in the community.